A Modified Lysimeter Study for Phyto-Treatment of Moderately Saline Wastewater Using Plant-Derived Filter Bedding Materials - Marathe, Deepak; Raghunathan, Karthik; Singh, Anshika; Thawale, Prashant; Kumari, Kanchan (Frontiers in Microbiology, 2021)
The present study focuses on determining the phyto-treatment efficiency for treatment of moderately saline wastewater using organic raw materials like rice husk, coconut husk, rice straw and charcoal. The moderately saline wastewater with TDS concentration up to 6143.33±5.77 mg/L was applied to the lysimeters at the rate of 200 m3 ha-1 day-1 in 5 different lysimeter treatments planted with Eucalyptus calmaldulensis (T1, T2, T3, T4 and T5). Each treatment showed significant treatment efficiency. Treatment T3 had highest removal efficiency of 76.21% followed by T4 (67.57%), T5 (65.18%), T2 (46.46%), and T1 (45.5%). T1 was control without filter bedding material; T2 had rice straw; T3 had rice husk, T4 had coconut husk and T5 had charcoal as the filter bedding material. T3 and T4 also showed higher salt accumulation such as (Sodium (Na) and Potassium (K). Further, Total Dissolved Solids (TDS), Chemical Oxygen Demand (COD), and Biological Oxygen Demand (BOD) was significantly reduced from wastewater in T3 and T4 treatment in comparison to other treatments. Also, Eucalyptus calmaldulensis plant species showed good response to wastewater treatment in terms of growth parameters such as root/shoot weight and NPK uptake, plant height, biomass and the chlorophyll content. However, most promising results were obtained for T3 and T4 treatments in comparison to control (T1). Findings of the study suggest that organic raw material-based amendments in lysimeter study are useful in managing the high salts levels in both plants and leachates.